Construction of a Training Content System for New Nurses in Cancer Hospital Based on Competency - Liu, Miao; Geng, Jingzhi; Gao, Jian; Mei, Zhihong; Wang, Xueyan; Wang, Sicong; Liu, Yan (Frontiers in Surgery, 2022)
【Abstract】 Objective To construct the training content system of new nurses in cancer hospital based on post competency, and to provide guidance for clinical new nurse training. Methods Through literature review, semi-structured interviews and questionnaire survey, a new draft of nurse training content system was initially established, and 17 experts were selected to make two rounds of inquiry on the system by Delphi method, so as to construct a new nurse training content system. Results The effective recoveries rate of the two rounds of expert correspondence was 100.00%, the cooperation among experts was high, and the authoritative coefficient of experts was 0.89. The content system of new nurse training constructed included 2 first-class indexes, 5 second-class indexes and 45 third-class indexes. Conclusion The new nurse training content system is closely combined with clinical work, pays attention to improving nurses' post competence, reflects the characteristics of nursing work in cancer hospitals, has a certain scientific and practical significance, and can provide guidance for the training of new nurses in cancer hospitals.